2016
DOI: 10.3399/bjgp16x688345
|View full text |Cite
|
Sign up to set email alerts
|

Population health needs as predictors of variations in NHS practice payments: a cross-sectional study of English general practices in 2013–2014 and 2014–2015

Abstract: BackgroundNHS general practice payments in England include pay for performance elements and a weighted component designed to compensate for workload, but without measures of specific deprivation or ethnic groups.AimTo determine whether population factors related to health needs predicted variations in NHS payments to individual general practices in England.Design and settingCross-sectional study of all practices in England, in financial years 2013–2014 and 2014–2015.MethodDescriptive statistics, univariable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…At the low-geography level, patient age, sex, ethnicity, morbidity (CMI), deprivation (IMD) and rurality explained a higher level of variation in funding than a previous model at the practice level for England [ 32 ]. More importantly, unlike in previous work at the practice level, we found the expected positive associations between funding and patient morbidity, deprivation and age.…”
Section: Discussionmentioning
confidence: 99%
“…At the low-geography level, patient age, sex, ethnicity, morbidity (CMI), deprivation (IMD) and rurality explained a higher level of variation in funding than a previous model at the practice level for England [ 32 ]. More importantly, unlike in previous work at the practice level, we found the expected positive associations between funding and patient morbidity, deprivation and age.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similarly, GP payments in England have been found to correlate negatively with some healthcare need predictors, such as deprivation, non-white ethnicity, and multimorbidity. 33 However, neither study included secondary care outcomes or financial modelling in their analyses. An observational study examining the relationship between funding, contract status, and QOF score in general practices found that GMS practices were the most efficient, achieving higher QOF scores with less funding.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…It has produced 48 prevalence estimates that reflect the pooled burden of need experienced by the dementia populations of six research studies conducted in The Netherlands, UK, Poland, Ireland, Germany, Norway, Portugal, Italy and Sweden. These outcomes are of interest as needs can lead to someone being put at risk of adverse outcomes including increased multi-morbidity (Levene et al, 2017;Seden, 2016). Therefore, greater understanding of these needs and the priority placed upon them by people with dementia and their informal caregivers, can inform the design of services to ensure they are person-centred, rather than disease focused.…”
Section: Discussionmentioning
confidence: 99%